Notes on the Newly Discovered Population of Sind Jerdon’s Babbler Chrysomma altirostre scindicum in Harike Wildlife Sanctuary, Punjab, India - Sawant, Saurabh; Sudhagar, M. (Journal of the Bombay Natural History Society (JBNHS), 2013)
Jerdon’s Babbler Chrysomma altirostre is native to India, Pakistan, and Myanmar, and is classified as Vulnerable by IUCN. The western race of the species, namely scindicum, was known only from a few localities in the floodplains of the Indus river and its tributaries in Pakistan, till it was recorded in Harike Wildlife Sanctuary, Punjab, India, in October 2012. During a follow-up study in Harike in December 2012, 33 individuals were recorded, which suggested that Harike wetland could have a significant population of this species and the subspecies scindicum in India. The assemblage of tall, dense, long, and unbroken grass stands of Phragmites-Saccharum-Imperata were found to be important for the species. This paper discusses the observations and localities where the birds were recorded, and the sonograms of their calls and songs.